The Fisher King [videorecording (DVD)] - Gilliam, Terry; Williams, Robin, 1951-2014; Bridges, Jeff, 1949-; Ruehl, Mercedes (Columbia TriStar Home Video, 2006)
Parry is a homeless history professor who lives in a fantasy world of castles, knights, and damsels in distress. Jack is New York's #1 shock deejay, whose arrogance triggers a tragedy that ruins his career. Penniless and without prospects, Jack finds himself plucked from disaster by the most improbable of saviors - Parry. Together, they begin a modern quest for redemption and the Holy Grail.